Case report: A rare case of delayed drug-induced hyponatremia in recurrent upper tract urothelial carcinoma following GC and Tislelizumab treatment - Wang, Zhi-Jie; Nie, Ying-Fang; Liang, Shi-Bing; Zhou, Jing; Hao, Shu-Lan; Liu, Li-Kun (Frontiers in Oncology, 2025)
Drug-induced hyponatremia is an adverse reaction with accelerated electrolyte disturbance. This study reported a rare case of delayed hyponatremia in a 68year-old female with recurrent upper tract urothelial carcinoma after Gemcitabine plus Cisplatin (GC) and Tislelizumab treatment. She had left ureter surgery, recurrence a year later with mildly abnormal kidney function (glomerular filtration rate (GFR) was 54.9 ml/min). After the first cycle of GC plus Tislelizumab, severe hyponatremia leading to life-threatening conditions occurred eight days later. Hypothesizing Cisplatin as the cause, its usage was modified in the second cycle (40mg/day for three days). No severe hyponatremia followed. CT showed partial remission. From the third cycle, due to grade IV bone marrow suppression, she had Tislelizumab alone. Now, she is on 21-day Tislelizumab maintenance with a stable tumor status. Low-dose continuous Cisplatin may suit patients with borderline or mildly abnormal renal function (GFR: 40-60mL/min) better than single full-dose use. Tislelizumab alone for maintenance may be an option for those intolerant of chemotherapy. But Na+ decrease may be related to Tirelizumab or Gemcitabine, needing more clinical observation and experiments.